2021
DOI: 10.17275/per.21.14.8.1
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Turkey’s PISA 2018 reading literacy scores within student-level and school-level variables

Abstract: The purpose of the current study was to investigate both student-level and school-level factors influencing reading literacy of students in Turkey by using PISA 2018 data. The study focused on reading literacy since the main subject of PISA 2018 was selected as reading literacy. The design of the study is a correlational research examining the relationship between student and school variables and reading literacy. The stratified random sample consisted of 6890 15-year students from 186 different schools. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
3
15
1
2
Order By: Relevance
“…Therefore, while interpreting these findings, one should consider that primary school children may not have enough maturity and life experiences to evaluate whether they like to read or not in a realistic way. As a matter of fact, studies conducted on older age groups show that reading enjoyment is one of the predictors of reading success, confirming the findings of this study (Cheema, 2018;Ertem, 2020;Rogiers, Van Keer & Merchie, 2020;Tavşancıl, Yıldırım, & Demir, 2019). Students who have positive attitudes and feelings towards reading spend more time on reading in their daily lives (Özbay, Bağcı & Uyar, 2008;Wilkinson et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, while interpreting these findings, one should consider that primary school children may not have enough maturity and life experiences to evaluate whether they like to read or not in a realistic way. As a matter of fact, studies conducted on older age groups show that reading enjoyment is one of the predictors of reading success, confirming the findings of this study (Cheema, 2018;Ertem, 2020;Rogiers, Van Keer & Merchie, 2020;Tavşancıl, Yıldırım, & Demir, 2019). Students who have positive attitudes and feelings towards reading spend more time on reading in their daily lives (Özbay, Bağcı & Uyar, 2008;Wilkinson et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…Findings from previous studies using PISA data that focused on students in countries other than the U.S. and Korea, including schools with a higher proportion of lower-level socioeconomic students and schools with a shortage of educational materials, tended to show relatively low academic achievement (Ertem, 2020;Perry & McConney, 2010). 'School size' is positively related 11(3)…”
Section: The Variables Predicting Reading Literacymentioning
confidence: 95%
“…Based on findings for students in other countries (e.g., Australia, China, Finland, France, Mexico, New Zealand, Singapore, Turkey) using PISA data, 'students' grade repetition' (Dong & Hu, 2019), 'fear of failure' (Koyuncu & Fırat, 2020), 'fixed mindset' (Claro et al, 2016), and 'ICT availability at school' (Xiao & Hu, 2019) were found to negatively influence reading literacy. Moreover, 'perceived emotional support from parents' and 'schools' classroom disciplinary climate' are significantly positively associated with students' academic achievement (Ertem, 2020). However, 'cooperation at school' is negatively related to students' reading literacy (Ertem, 2020).…”
Section: The Variables Predicting Reading Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the PISA results in 2012, 2015 and 2018, variables affecting student performance in the Turkish sample include fairness and effectiveness in educational resources, school resources, socio-economic level, pre-school education period, educational background, gender, motivation, self-efficacy, school income, reading habits, and emotional support of the family. These variables are based on the factors such as the number of mathematics teachers and the number of students in the school, computer usage opportunities, the mother's working status, having a computer at home, the students having a room of their own, and the number Mimbar Sekolah Dasar, Volume 8 Number 3 December 2021 [235] of books at home (Acar & Öğretmen;Özer-Özkan & Acar-Güvendir, 2014;Aksu et al, 2017;Ertem, 2021;Türkan et al, 2015;Arıcı & Altıntaş, 2014;Güzeller & Şeker, 2016).…”
mentioning
confidence: 99%